(untitled) (The Agriculturists, 2012)
In the present investigation attempts were made to estimate genetic parameters for yield and its components in 315 genotypes of cocoyam collected from thirteen aroid growing districts. Plant height, petiole length, petiole breadth, leaf number, leaf length, leaf breadth, LAI, Inflorescence length, peduncle length, spathe length, spathe breadth, corm length, corm breadth, cormel number, cormel length, cormel breadth, corm weight, cormel weight, total fresh weight, total dry weight, yield per plant were taken in this study. Presence of significant differences together with wide ranges of variation indicates wide range of variability existed among the genotypes of cocoyam. Genotypic variances and coefficient of variation for most of the characters were remarkably higher than their corresponding environmental variances, which also indicate the existence of variation in genotypic level. Plant height, petiole length, leaf length, leaf breadth for cocoyam expressed high heritability with moderate to high genetic advance signalled heritable in nature. High heritability with high genetic advance in percentage of mean was also observed for plant height, petiole length, DOI: http://dx.doi.org/10.3329/agric.v10i2.13150 The Agriculturists 2012; 10(2) 127-132